2009
DOI: 10.1007/s11998-008-9155-z
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to graft siloxanes to alkyds

Abstract: The effect of oil length of alkyds and substitution of siloxane backbone has been studied for alkyd-siloxane hybrids. A series of nine alkydsiloxane hybrids were synthesized by either varying the oil length of the alkyd or the siloxane backbone substitution. Three linseed oil-based alkyds with either a long, medium, or short oil length were grafted with three hydride-terminated siloxanes substituted with methyl, cyclopentyl, or cyclohexyl groups. A hydrocoupling reaction was used to couple the telechelic silox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…One of the limitation of the alkyd is their poor outdoor weatherability that could be improved by adding silicones which possess excellent moisture and UV-degradation resistance. 16,107 Indeed, silicones, also called polysiloxanes, are a popular group of synthetic polymers providing hydrophobicity to coatings thanks to their siloxane groups (Si-O-Si). 108 Moreover, silicone containing polymers are attractive because they exhibit low surface tension, excellent electrical properties, good weatherability, non-flammability, high gas permeability, good thermal and chemistry stability, as well as corrosion protection.…”
Section: Polysiloxanementioning
confidence: 99%
See 2 more Smart Citations
“…One of the limitation of the alkyd is their poor outdoor weatherability that could be improved by adding silicones which possess excellent moisture and UV-degradation resistance. 16,107 Indeed, silicones, also called polysiloxanes, are a popular group of synthetic polymers providing hydrophobicity to coatings thanks to their siloxane groups (Si-O-Si). 108 Moreover, silicone containing polymers are attractive because they exhibit low surface tension, excellent electrical properties, good weatherability, non-flammability, high gas permeability, good thermal and chemistry stability, as well as corrosion protection.…”
Section: Polysiloxanementioning
confidence: 99%
“…In order to overcome this drawback, siloxanes were grafted to alkyds, thus the microphase separation was reduced, leading to better overall properties. 16 Several routes were investigated to create covalent bonds between constituents. Alkyd resins can be post-functionalized by silicon compounds thanks to their remaining hydroxyl groups or by chemically modified unsaturations present in their long aliphatic chains in order to obtain silicone-modified alkyd resins.…”
Section: Polysiloxanementioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized resin was reacted with 0.7 mole di-ethanolamine at 65 ± 2 • C for 1 h, neutralized with phosphoric acid solution and stirring continued for 6 h. The prepared waterborne resin was dried using cobalt based driers (blend of lead (0.3% of metal), cobalt (0.03% of metal) in the ratio 10:1 (Lead: cobalt)). This cobalt and lead based driers are most extensively used for drying waterborne coatings [23][24][25][26][27]. The viscosity and non volatile matter (NVM) of resin were adjusted with water.…”
Section: Synthesis Of Waterborne Epoxy Estermentioning
confidence: 99%
“…Different composites comprising s-triazine and organosilicone substrates are exploited in coatings, adhesives, cosmetics and other products [16][17][18][19][20]. In a recent study, we concluded that s-triazine (▲) can be conveniently bonded to a series of organosilicone moieties (RSiO 1.5 , R 2 SiO, R = CH 3 and C 6 H 5 ) through -O-connections to form intact oligomeric glassy materials, Fig.…”
Section: Introductionmentioning
confidence: 99%